ABOUT ANATOLY YAKOBSON AND HIS TRANSLATIONS OF HOVHANNES TUMANYAN’S POEMS - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2019)
The article presents and describes the life and multilateral works of Anatoly Yakobson, one of Russian translators of Hovhannes Tumanyan’s poems. The activity in the sphere of human rights forced him in 1973 to emigrate from homeland and settle in Israel, which in the future led to the suicide. The author of the article defines the principles of Yakobson as a translator and demonstrates by various examples that in his translations Yakobson delicately recreatedstylistic and artistic peculiarities of the original texts.
Keywords: Yakobson, personality, human righth activist, emigration, Tumanyan, translation principles, penetration into the original, artistic adequacy.